Laser capture microdissection for the analysis of gene expression during embryogenesis of Arabidopsis - Casson, S.; Spencer, M.; Walker, K.; Lindsey, K.
It is during embryogenesis that the body plan of the developing plant is established. Analysis of gene expression during embryogenesis has been limited due to the technical difficulty of accessing the developing embryo. Here we demonstrate that laser capture microdissection can be applied to the analysis of embryogenesis. We show how this technique can be used in concert with DNA microarray for the large-scale analysis of gene expression in apical and basal domains of the globular-stage and heart-stage embryo, respectively, when critical events of polarity, symmetry and biochemical differentiation are established. This high resolution spatial analysis shows that up to approximately 65
Keywords: ARABIDOPSIS THALIANA; LASER CAPTURE MICRODISSECTION; EMBRYOGENESIS; DNA MICROARRAY; TRANSCRIPTOME; GENE EXPRESSION